2005
DOI: 10.1002/cne.20797
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal transition zone/rostral ventromedial medulla connections and facilitation of orofacial hyperalgesia after masseter inflammation in rats

Abstract: Recent studies have implicated a role for the trigeminal interpolaris/caudalis (Vi/Vc) transition zone in response to orofacial injury. Using combined neuronal tracing and Fos protein immunocytochemistry, we investigated functional connections between the Vi/Vc transition zone and rostral ventromedial medulla (RVM), a key structure in descending pain modulation. Rats were injected with a retrograde tracer, FluoroGold, into the RVM 7 days before injection of an inflammatory agent, complete Freund's adjuvant, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
84
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 63 publications
(112 reference statements)
11
84
1
1
Order By: Relevance
“…Furthermore, the number of nociceptive neurons that can be analyzed in single-neuron recording studies is limited in any one animal. It is probable that these fiber differences and technical limitation in single-neuron recording may be involved in the distribu- Generally, we observed a pattern of organization of pERK-LI cell expression following capsaicin stimulation of the face that was similar to that reported in previous c-Fos studies Zhou et al, 1999;Takemura et al, 2000;Watanabe et al, 2002;Nomura et al, 2002;Bereiter et al, 2005;Sato et al, 2005;Sugiyo et al, 2005Sugiyo et al, , 2006. However, the distribution of pERK-LI cells was more restricted from the Vi/Vc zone through the Vc/C2 zone compared with previous reports of c-Fospositive neurons Mineta et al, 1995).…”
Section: Dorsoventral and Rostrocaudal Organization Of Perk-li Cellssupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, the number of nociceptive neurons that can be analyzed in single-neuron recording studies is limited in any one animal. It is probable that these fiber differences and technical limitation in single-neuron recording may be involved in the distribu- Generally, we observed a pattern of organization of pERK-LI cell expression following capsaicin stimulation of the face that was similar to that reported in previous c-Fos studies Zhou et al, 1999;Takemura et al, 2000;Watanabe et al, 2002;Nomura et al, 2002;Bereiter et al, 2005;Sato et al, 2005;Sugiyo et al, 2005Sugiyo et al, , 2006. However, the distribution of pERK-LI cells was more restricted from the Vi/Vc zone through the Vc/C2 zone compared with previous reports of c-Fospositive neurons Mineta et al, 1995).…”
Section: Dorsoventral and Rostrocaudal Organization Of Perk-li Cellssupporting
confidence: 81%
“…Another approach that has been used is c-Fos labeling to delineate the arrangement of nociceptive neurons in the trigeminal spinal nucleus and upper cervical cord as well as spinal dorsal horn. After noxious stimulation of a variety of orofacial sites, Fos protein like-immunoreactive cells (Fos-LI cells) occur in the trigeminal spinal nucleus interpolaris (Vi) and caudalis (Vc) transition zone (Vi/Vc zone) and the Vc/C2 transition zone Iwata et al, 1998a;Zhou et al, 1999;Takemura et al, 2000;Nomura et al, 2002;Watanabe et al, 2002;Kawabata et al, 2004;Bereiter et al, 2005;Sato et al, 2005;Sugiyo et al, 2005Sugiyo et al, , 2006Shimizu et al, 2006) in a somatotopic arrangement, and their numbers increase as noxious stimulus intensity increases Mineta et al, 1995). However, it has been reported that the c-Fos expression starts at about 30 minutes and peaks about 1 hour after noxious stimulation (Hunt et al, 1987;Tokunaga et al, 1995) in both superficial and deep laminae of the spinal dorsal horn (DH; Bullitt, 1991), so it is very likely that c-Fos expression is not directly correlated with an activation of Vc and upper cervical nociceptive neurons following acute orofacial noxious stimulation.…”
Section: Indexing Terms: Somatotopic Organization; Nociceptive Neuronmentioning
confidence: 98%
“…Local anesthesia of RVM attenuates mustard oilinduced hyperexcitability of spinal dorsal horn neurons [16] and behavioral hyperalgesia [17]. Lesions of the RVM suppress formalin-induced nocifensive behavior [18], inhibit secondary hyperalgesia produced by topical application of mustard oil [15], and attenuate (secondary) mechanical hyperalgesia after masseter muscle inflammation induced by complete Freund's adjuvant (CFA) [19]. The same phenomenon occurs in models of neuropathic pain.…”
Section: Pain Modulatory Circuitry and Behavioral Hyperalgesiamentioning
confidence: 85%
“…Following injection of the retrograde tracer Fluorogold into the Vi/Vc transition zone, retrogradely labeled cells were observed in the Vc/C1,2 region (Sato et al ., 2005). After lesions of the bilateral Vc, there is a selective reduction of inflammation-induced Fos-expressing neurons in the ventral Vi/Vc, but not in dorsal or intermediate Vi/Vc, or nucleus tractus solitarius (Sugiyo et al ., 2005). These findings support that trigeminal transition zone activity, particularly the ventral Vi/Vc, is modulated by the activation of the caudal laminated Vc zone.…”
Section: Functional Input and Output Of The Vi/vc Transition Zonementioning
confidence: 99%